COOLING SYSTEMS OF MILK, FRUIT AND VEGETABLES STORAGE WITH LOW CONSUMPTION OF ENERGY - Volkonovich L.; Kiorsak M.; Turkuman L.; Volkonovich A.; Oprea D.; Rotari V.; Slipenchi V (Problems of the Regional Energetics)
Article is devoted to use of a natural cold for cooling milk and fruit and vegetables storage. The analysis of the block diagrams, description of storehouses and the curves of temperature and air humidity changes for various types of cooling systems are given; the analysis of quality of vegetables and fruit and energy expenses per unit of production are done, which prove the efficiency of the offered systems.